2017
DOI: 10.14527/pegegog.2017.010
|View full text |Cite
|
Sign up to set email alerts
|

Purposes and characteristics of internet use of adolescents

Abstract: The aim of this study is to determine the purposes and characteristics of adolescents' internet use. Furthermore, the study compared adolescents' internet use purposes in terms of gender, school type and grade level variables. The study group consisted of 1002 students who were studying in 10 public high schools in 2012-2013 academic year in İstanbul. The data were collected through the Internet Use Purposes Scale (IPUS) and were analyzed using descriptive statistics, t-test and ANOVA. Research revealed that d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
3
0
1
Order By: Relevance
“…Similarly, having more than one profile is closely related to liking because individuals tend to be involved more in environments where they are admired and accepted. The effects of this situation on adolescents were also reported in a study conducted by Akar (2017). The researcher found that, due to the problems experienced by adolescents regarding adaptation to their environment, they used social networks more for the purpose of making friends and meeting their needs for socialization and that these adolescents were at risk of Internet addiction.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Similarly, having more than one profile is closely related to liking because individuals tend to be involved more in environments where they are admired and accepted. The effects of this situation on adolescents were also reported in a study conducted by Akar (2017). The researcher found that, due to the problems experienced by adolescents regarding adaptation to their environment, they used social networks more for the purpose of making friends and meeting their needs for socialization and that these adolescents were at risk of Internet addiction.…”
Section: Discussionmentioning
confidence: 81%
“…Bu durumun ergenler üzerindeki etkilerini Akar (2017)'ı çalışmasında görebilmek mümkündür. Akar (2017); ergenlerin çevreye olan uyumsuzluklarından dolayı arkadaş olma ve sosyalleşme ihtiyaçlarını karşılamak için daha fazla sosyal ağ kullandıklarını ve internet bağımlılığı için risk grubunda bulunduklarını belirtmektedir. Ergenlerin sosyal ağları gerçek dünyaya alternatif bir ortam olarak tercih etmelerinin yanı sıra sosyal ağlar aynı zamanda etkili bir öğrenme ortamıdır.…”
Section: Discussionunclassified
“…In the literature of our country, there are various measurement instruments used to examine the internet usage behaviors of college students (Kabadayı, 2020). When these measurement instruments were examined, it was found that these were the tools only to determine university students' internet addiction (Çakır-Balta & Horzum, 2008;Kesici & Şahin, 2010;Kutlu et al, 2016), problematic internet use (Deniz & Tutgun-Ünal, 2016;Göktaş et al, 2018), or purposes of the internet usage (Akar, 2017;Karal & Kokoç, 2010;Usluel et al, 2014). Apart from these measurement tools, there are some measurement instruments aimed at measuring the internet usage habits of university students.…”
Section: Introductionmentioning
confidence: 99%
“…Internet use and abuse can lead to Internet addiction in approximately 10 to 20% of users (Akar, 2017;Milková and Ambrožová, 2018). In addition, there are certain risks of Internet use related to problematic Internet use, such as cyberbullying, cyber dating abuse, online grooming, or sexting (Machimbarrena et al, 2018).…”
Section: Introductionmentioning
confidence: 99%